Pengembangan Model Pembelajaran Berbasis CTL untuk Meningkatkan Kompetensi Menggambar Berbantuan Komputer (CAD) Siswa SMK - Febrianto Amri Ristadi; Yatin Ngadiyono (Department of Mechanical Engineering Education, 2017)
This research aims to define a construct of CTL-based learning model on CAD subject. The learning model is intended for vocational high school students to improve their CAD competence. The research method being used was Research and Development methods implementing Dick and Carrie's approach. The research was carried out in Bantul and Kulonprogo district. The subject was SMK students underwent CAD subject learning. The result of the large-scale test shows that the CAD learning model is appropriate to be implemented in the CAD teaching and learning. The modul gained a strong positive response from the students in the functional and benefit aspects, with an average score of 24.42. The modul also gained a strong positive response from the attractiveness aspect with an average score of 37.73. Students also found that it is very appropriate in the learning material aspect, shown by an average score of 30.70. The CAD learning methods can be implemented by following the steps of defining Basic Competencies, subject materials and objects, motivating the students by assosiating the learning material with environmental context, determining heterogeneous group and administering task, group discussion, individual task, assessment, reflection and feedbacks. The CAD learning implementing the CTL-based modul evidently improves the students' achievement by 19%, from 71.18 to 84.64. Tujuan penelitian ini adalah menemukan konstruksi model pembelajaran berbasis CTL pada mata diklat CAD. Metode penelitian yang diterapkan adalah penelitian pengembangan dengan pendekatan Dick & Carie. Penelitian dilakukan di Bantul dan Wates, Kulon Progo. Subyek penelitian adalah siswa SMK yang menempuh mata diklat CAD. Hasil uji coba pada skala besar menunjukkan bahwa modul CAD layak untuk diterapkan dalam uji coba pembelajaran CAD. Modul mendapatkan kategori respons sangat layak dari siswa untuk: (a) aspek fungsi dan manfaat dengan skor rerata 24,42 , (b) aspek kemenarikan dengan skor rerata 37,73 , (c) aspek materi pembelajaran dengan skor rerata 30,70. Metode pembelajaran CAD ditempuh dengan urutan sebagai berikut: (1) menentukan KD, (2) menentukan materi, (3) menentukan benda/obyek, (4) memotivasi dengan mengaitkan materi ajar dengan konteks lingkungan, (5) penentuan kelompok heterogen, pemberian tugas, (6) diskusi kelompok, (7) tugas mandiri, (8) penilaian, (9) refleksi hasil dan umpan balik. Pembelajaran CAD menggunakan modul berbasis CTL dapat meningkatkan prestasi sebesar 19%, atau dari 71.18, menjadi 84.64.